2019
DOI: 10.1007/s40145-018-0307-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and thermal stability of carbon fiber cloth reinforced sol-derived mullite composites

Abstract: For the wide application as thermal protection materials, it is very necessary for mullite ceramics to improve fracture toughness. In this paper, the laminated and stitched carbon fiber cloth preform reinforced mullite (C/mullite) composites were prepared through the route of sol impregnation and heat treatment using the Al 2 O 3 −SiO 2 sol with a high solid content as raw materials. The C/mullite composites showed a flexural strength of 228.9 MPa that was comparable to that of dense monolithic mullite althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Svetlana et al 37 found that, with increasing temperature, solid solubility of Fe 2 O 3 in mullite was gradually increased, and solubility of up to 7.6 wt% at 1300°C. It is also reported that Fe 3+ ions could enter the crystal lattice of mullite, forming stable solid‐solutions at high temperatures 4,12,38 …”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…Svetlana et al 37 found that, with increasing temperature, solid solubility of Fe 2 O 3 in mullite was gradually increased, and solubility of up to 7.6 wt% at 1300°C. It is also reported that Fe 3+ ions could enter the crystal lattice of mullite, forming stable solid‐solutions at high temperatures 4,12,38 …”
Section: Introductionmentioning
confidence: 98%
“…Mullite is an excellent ceramic material due to the unique properties, such as low coefficient of thermal expansion, high corrosion resistance to acid and alkali, high‐temperature creep resistance, strong thermal shock resistance, high chemical and thermal stability, high permeability, and excellent mechanical properties 1–3 . Mullite ceramics have been widely utilized as metallurgical, glass, ceramic, and other industrial refractory materials 4–6 . They are also widely used as heat‐resistant materials, such as crucibles, protective tubes, and thermocouple tubes for electronic packaging 7–9 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since mullite (3Al2O3•2SiO2) exhibits a similar thermal expansion coefficient to SiC [24], better mechanical properties, good oxidation/corrosion resistance and thermal stability [25,26], aluminium sources are introduced to react with the oxidation-derived SiO2 and form mullite phase. Aluminium source includes alumina [27][28][29], Kaolin [30], aluminium hydroxide [31,32], bauxite [33], fly ash [22,34] and aluminium isopropoxide [35].…”
Section: Introductionmentioning
confidence: 99%